The veteran's PTSD handbook how to file and collect on claims for post-traumatic stress disorder - Roche, John D. Maj (Potomac Books, 2007)
From the author of The Veteran's Survival Guide, The Veteran's PTSD Handbook addresses the obstacles that veterans face when filing for benefits related to post-traumatic stress disorder (PTSD). One of the greatest obstacles, John Roche writes, is establishing a connection between a veteran's service and PTSD. Because both combat stressors and noncombat stressors can cause PTSD and because of the difficulties in diagnosing the condition, filing a successful claim for benefits based on PTSD is difficult. In the same accessible, self-help style used in The Veteran's Survival Guide, Roche offers.